(untitled) (Journal of Universal Science Research, 2023)
Digital medical images are one of the sources of information for timely prevention of possible diseases. In this case, color medical images are widely used. One example of such use is in the diagnosis of fatty liver disease. Based on this, the paper considers the possibility of studying fatty liver disease based on digital image segmentation taking into account color. The results of digital processing are presented for real images depicting lesions of fatty liver disease.